Working with the Elite: the Intersection of Social Work and Corporate Foundations - the Case of Zuellig Family Foundation - Nazal, Suzanne Magalona; Dizon, Nadya Ysabelle; Endaya, Quiel Alec Caguimbal (Indonesian Social Work Consortium (ISWC), 2023)
Social Work draws from various disciplines but is perceived to be the direct opposite of corporate work, however, there is a need to work with the elite for the sake of social development due to their available resources and skills that social workers lack. While Corporate Social Responsibility typically takes the form of dole-outs on a voluntary basis, it has begun to transition into building partnerships with communities. Data from the Local Health System program of Zuellig Family Foundation was examined to (a) describe the developmental principles used by an elite foundation for the development and implementation of their program, (b) determine the intersection of the operations of the program with the Empowerment Theory and Developmental Perspective as practiced by the Social Work profession, and (c) discuss the role of social workers in corporate-led programs. Despite the surface differences of social work and corporate work, foundations of the elite can be effective contributors to social change and development, and can work with the Social Work profession in empowering communities that suffer from inequities. The findings of the study indicate that social work professionals and other humanities professions must explore partnerships with corporate-led foundations to deepen knowledge bases and ensure social development. Keywords: Social Work profession, Corporate Social Responsibility, Empowerment Theory, Developmental Perspective, Zuellig Family Foundation, Local Health System, partnership